Analysis of the Effectiveness of Fitness Programs «Health and Development during War» on the Physical and Mental Health of Students - Mozolev, Oleksandr; Khmara, Maryna; Bodnar, Alina (Pedagogical Discourse, 2025)
Maintaining students’ physical and psychological health during wartime is a complex and ambiguous pedagogical process, the effectiveness of which is additionally influenced by many factors. The aim of the article is to analyze the effectiveness of the physical education and health program «Health and Development during War» on the physical and mental health of students. The participants of the experiment: 226 students aged 17–19 (147 women and 79 men) of Khmelnytskyi Humanitarian-Pedagogical Academy. Methods: analysis of scientific and methodological sources; questionnaire; survey; pedagogical observation; methodology for studying the functional, physical and psychological state of students; comparative analysis; methods of mathematical statistics. The results of the study showed that students experienced positive changes in their physical health: functional indicators of the development of the respiratory system, physical performance of the cardiovascular system, as well as indicators of recovery processes after physical exertion improved. In the development of students’ physical abilities, significantly significant changes occurred in the indicators of development, speed-strength qualities and general coordination of movement. Other indicators of physical development remained at the previous level. Analysis of students’ psychological health shows that the processes of psychological adaptation to war are different for men and women. Women experience significant fluctuations in their psychological state, while men’s psychological state is more stable. It has been established that physical exercise and communication help reduce depression, boost emotional uplift, improve mood and overall psychological well-being. Conclusions. The «Health and Development during War» program is adapted to the education of students in the conditions of martial law in Ukraine. It has a positive effect on the development of students’ functional and physical abilities, and helps stabilize their psychological state.